'Modern Madonnas' – 13 Artists respond to the 'Mother and Child' theme St. George's Arts, St. George's Church, Esher, Surrey, UK 26 May – 17 June, 2012. Issue 2 (2012) - Baillie, Rebecca
No abstract available